Application of Artificial Bee Colony Algorithm to Optimize The Shortest Route to Distribute Clean Water Pipes - Mhd Furqan; Yusuf Ramadhan Nasution; Khairunnisa Khairunnisa (Yayasan Literasi Sains Indonesia, 2022)
Regional Water Company Tirtanadi is a company engaged in clean water treatment and distributing clean water into the customers’ houses. The pipelines used are long and branched which causes the water volume to be divided. So, the alternative solution offered, to make sure the water distribution to each customers’ houses are efficient, is to search the shortest route using the Artificial Bee Colony algorithm. Artificial Bee Colony algorithm is a metaheuristic algorithm which has a strong global search ability and is able to solve continuous problems on determining the optimal clean water pipe route. This research’s goal is to facilitate Tirtanadi company on deciding the best installation point for the clean water distribution pipe. This research uses a dataset in the form of 8 installation points and one water treatment plant point. According to the calculation result on determining the best water pipe route using the Artificial Bee Colony algorithm obtained an optimal route which is V1→V7→V4→V9→V8→V2→V6→V3→V5. So it can be concluded that Artificial Bee Colony Algorithm is able to decided the search for clean water distribution pipes route on PDAM Tirtanadi and is able to give a good solution for searching for the shortest route.